Explanation and Elaboration Document for the STROBE‐Vet Statement: Strengthening the Reporting of Observational Studies in Epidemiology—Veterinary Extension. (7th November 2016) - O'Connor, A.M.; Sargeant, J.M.; Dohoo, I.R.; Erb, H.N.; Cevallos, M.; Egger, M.; Ersbøll, A.K.; Martin, S.W.; Nielsen, L.R.; Pearl, D.L.; Pfeiffer, D.U.; Sanchez, J.; et al.
Abstract : The STROBE (Strengthening the Reporting of Observational Studies in Epidemiology) statement was first published in 2007 and again in 2014. The purpose of the original STROBE was to provide guidance for authors, reviewers, and editors to improve the comprehensiveness of reporting; however, STROBE has a unique focus on observational studies. Although much of the guidance provided by the original STROBE document is directly applicable, it was deemed useful to map those statements to veterinary concepts, provide veterinary examples, and highlight unique aspects of reporting in veterinary observational studies. Here, we present the examples and explanations for the checklist items included in the STROBE‐Vet statement. Thus, this is a companion document to the STROBE‐Vet statement methods and process document (JVIM_14575 "Methods and Processes of Developing the Strengthening the Reporting of Observational Studies in Epidemiology—Veterinary (STROBE‐Vet) Statement" undergoing proofing), which describes the checklist and how it was developed.